Greener Dye Synthesis: Continuous, Solvent‐Free Synthesis of Commodity Perylene Diimides by Twin‐Screw Extrusion. Issue 11 (29th January 2020) - Cao, Qun; Crawford, Deborah E.; Shi, Chengcheng; James, Stuart L.
Abstract: A continuous, scalable, and solvent‐free method for the synthesis of various naphthalic imides and perylene diimides (PDIs) using twin‐screw extrusion (TSE) is reported. Using TSE, naphthalic imides were obtained quantitatively without the need for excess amine reactant or product purification. With good functional‐group tolerance, alkyl and benzyl amine derived PDIs (incl. commercial dyes) were obtained in 50–99 % yield. Use of K2 CO3, enabled synthesis of more difficult aniline‐derived PDIs. Furthermore, an automated continuous TSE process for Pigments Black 31 and 32 is demonstrated, with a throughput rate of about 1500 g day −1, corresponding to a space time yield of about 30×10 3 kg m −3 day −1, which is 1–2 orders of magnitude greater than for solvent‐based batch methods. These methods provide substantial waste reductions and improved efficiency compared to conventional solvent‐based methods. Abstract : Dye hard : Translating from a "beat and heat" method, a continuous, scalable, and solvent‐free method for the synthesis of various naphthalic imides (3 examples) and perylene diimides (PDIs, 21 examples) using twin‐screw extrusion (TSE) is reported. The TSE method provides substantial reductions in waste and improved efficiency compared to conventional solvent‐based methods.